Customer service and maintenance system - Shamsudin, Adam (2006)
Customer Service and Maintenance System is believed to be found under one of many modules of a Customer Relationship Management. It is crucial that the system to be developed in line with company’s business objectives. This is to ensure that the system is well developed, so that every part of the modules and functions will be fully utilized by the System Engineer, Managers, and Higher Management personnel. Apart from that, this project enables our participants to gather enormous amount of knowledge, not just in system development, but the whole process of managing every single phase of project development. This project is developed with the help of Unified Modeling Language as one of the development tool. The basic concept of this system is to promote the needs of catering the customer’s breakdown calls, and logging it into a nice and well-defined database. It helps the company to be at much competitive with the other multi-national organizations in terms of much higher service quality